SUPERCHARGING PRODUCTIVITY WITH TRELLO harness Trello's powerful features to boost productivity and team collaboration - Joiner, Brittany (Packt Publishing Ltd., 2023)
An expert's guide to unleash your productivity potential for work and personal projects with Trello automation, advanced features, integrations, and Power-Ups Purchase of the print or Kindle book includes a free PDF eBook Key Features Uncover the secrets of Trello's core features, automation, and integrations to become a Trello power user Master Trello with practical advice, real-world examples, and workflows to improve task management Get in-depth knowledge of Trello to get it up and running within minutes and scale it for future needs Book Description Managing large projects and teams can be an immense challenge, but having an efficient project management system can make all the difference. Trello is one of the leading project management systems, however, it's crucial to understand its features to leverage its full potential Supercharging Productivity with Trello is the perfect guide for you to enhance efficiency and do more in less time. You'll start by exploring Trello's structure, including cards, boards, and lists, before diving into Trello card basics. Next, you'll learn to use Trello views and templates to aggregate tasks and organize projects. You'll then explore automation, including triggers and actions, to create powerful workflows that will help you prioritize tasks and organize your data effectively. Later, you'll discover Power-Ups, an add-on that extends Trello's functionality. Throughout the book, you'll find practical tips and real-world examples to gain practical knowledge. By the end of this book, you'll be well-equipped to use Trello effectively for task and project management helping you stay on top of your game and deliver quick wins in no time. What you will learn Explore Trello's structure and the important features Customize Trello cards and fields to fit your use case Create Trello views to get a mile-high view of your projects Discover Trello's automation features to save time and automate tasks Use Power-Ups for documentation, reporting, contacts, and more Get the most out of Trello with real-world examples and practical tips Who this book is for If you are a busy professional, student, entrepreneur, or anyone looking to get more done in less time, this book is for you. Whether you're new or an experienced Trello user, this comprehensive guide will provide the tools and strategies needed to streamline your workflow, boost your productivity, and achieve your goals.